2020
DOI: 10.1186/s10194-020-01147-w
|View full text |Cite
|
Sign up to set email alerts
|

Low-value care practice in headache: a Spanish mixed methods research study

Abstract: Background: Headache is one of the most prevalent diseases. The Global Burden of Disease Study ranks it as the seventh most common disease overall and the second largest neurological cause of disability in the world. The "Do Not Do" recommendations are a strategy for increasing the quality of care and reducing the cost of care for headache. This study aimed to identify specific low-value practices in headache care, determine their frequency, and estimate the cost overrun that they represent, in order to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
1
Order By: Relevance
“…Three of 27 studies targeted paediatric hospitals or health services specifically 40–42. The entire continuum of care (primary care to specialist care or healthcare system) was covered by six records 19 43–47. Four of 27 records focused on practice by a specific profession or discipline40 48–50 with two records targeting practice by the allied health disciplines of nutrition50 and physical therapy 49.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three of 27 studies targeted paediatric hospitals or health services specifically 40–42. The entire continuum of care (primary care to specialist care or healthcare system) was covered by six records 19 43–47. Four of 27 records focused on practice by a specific profession or discipline40 48–50 with two records targeting practice by the allied health disciplines of nutrition50 and physical therapy 49.…”
Section: Resultsmentioning
confidence: 99%
“…There was variability in the order of the components applied across studies. Of the records that included expert consensus, committee member or stakeholder engagement activities, participants were mostly clinicians and sample sizes ranged from n=646 55 57 to n=22 48. Where reported, sample sizes in studies that accessed patient record data to identify the extent of the low-value care ranged from 1012 records in four participating hospitals55 to 62 314 admissions 51.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A decade ago, a study reported that only a small proportion of migraine patients received specific medications or preventive treatment in Spain, despite high levels of disability [ 38 ]. Our study findings suggest that undertreatment of migraine remains an issue, with only half of the patients receiving any treatment for migraine in the past 24 months [ 6 , 39 , 46 , 56 , 57 ]. In those who were treated, many were prescribed several acute and preventive treatments, suggesting an inadequate control.…”
Section: Discussionmentioning
confidence: 97%